How fertilizer application increased the number of marketable maize cobs and cassava storage root yields profitability in the cassava-maize intercropping system - CGIAR Research Program on Maize (2021)
Study concluded indicating that By investing in NPK fertilizers in cassava-maize intercropping systems, profitability can be achieved, however, this is contextual as it would depend on agroecology and market prices.